Farmers' Level of Knowledge of Financial Management in Rabbit Farming Businesses - Utami, Sri Wira; Sonjaya, Herry; Tullah, Muh. Firdaus; Irwan; Aksan, Muhammad; Rahmat R, Muh. Faisal (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2024)
The rabbit farming business is used as income for business sustainability and development and has the potential to be developed. Knowledge of financial management is important for farmers to manage their rabbit farms efficiently and obtain productive credit. Financial management in the livestock sector becomes very important if finance helps introduce important technologies that affect productivity in a timely manner The research aims to determine the level of knowledge of rabbit breeders in managing business finances. Data analysis uses the levels financial services authority is well literate, sufficient literate, less literate and not literate. The results show that financial management is in the < 60% category, which means the individual has category low financial knowledge is less literate. This shows that farmers' knowledge regarding financial management is still very low. This can be seen that the skills or abilities of breeders in financial management are still low. The ability to absorb new technology and business development in the global market for small and medium scale farms will be hampered if skills in management and simple financial management practices are respectively low. This is something that can hinder obtaining business financing.